Aplikasi Vaksin Dna Koi Herpes Virus (Khv) Melalui Metode Perendaman Dengan Dosis Yang Berbeda Dalam Upaya Pencegahan Penyakit Pada Ikan Mas (Cyprinus carpio) - Chairunnisa, Sekar Ayu; Prayitno, Slamet Budi; -, Sarjito; Santika, Ayi; Nuryati, Sri (Journal of Aquaculture Management and Technology, 2013)
The purpose of this research was to determine fish clinical signs of KHV-infected and determine effectiveness of KHV DNA vaccine with immersion method to prevent koi herpes virus (KHV) infection. This research was conducted in National Center for Freshwater Aquaculture Development (BBPBAT) Sukabumi, from October 2012 to Februari 2013. The fish samples used were carp seed free KHV with size 3 – 5 cm as many as 450 animals. Five (5) treatments and 3 replications were administered in this research. The treatment were, without vaccine, vaccine at dose of 104, 105, 106, and 107 CFU/ml. Vaccination technique used was vaccination through immersion method. One of the vaccine that has been developed was KHV DNA vaccine. Eksperimental fishes were maintain for 30 days past vaccination, and then challenged with KHV and observed for 21 days. The variables measured were clinical signs and survival rate. The results of this research indicated that non vaccinated fish (A), vaccinated fish at 104(B) and 105(C). demonstered clinical signs of KHV-infected fish, while vaccinated fish at 106(D) and 107(D) visibly normal. This results indicated that vaccination using KHV DNA vaccines at 106 and 107 CFU/ml could prevent eksperimental fish from KHV-infection. PCR results showed that fish with treatments A, B and C positive infected KHV, while treatment D and E negative KHV. Survival rate (SR) at treatment A (15,56%), B (50,00%), C (53,33%), D (78,89%) and E (83,33%). For prevention of KHV, dose vaccine DNA KHV 106 and 107 CFU/ml could be used. This results supported by survival rate from treatment D (78,89%) and E (83,33%) higher than treatment A, B and C.